KNOWLEDGE LEVEL REGARDING ANEMIA AMONG STUDENTS OF THE FACULTY OF HEALTH SCIENCES, UNIVERSITAS NAHDLATUL ULAMA SUMATERA UTARA - Nurul Amalia Sofyan; Aryeni Aryeni; M Zaidun Sofyan (Jurnal Ilmiah Keperawatan, 2026)
Background: Anemia is a global health problem with a high prevalence and is commonly experienced by adolescents. As prospective healthcare workers, students in the Faculty of Health Sciences are expected to have a sound knowledge of anemia as a basis for promotive and preventive efforts in the community. Purpose: This study aims to determine the level of knowledge of students at the Faculty of Health Sciences Universitas Nahdlatul Ulama Sumatera Utara about anemia. Methods: This study was a quantitative-descriptive study with a cross-sectional design. It involved 69 university students selected using a total sampling technique. Data collection used a validated 25-question questionnaire with "true" and "false" options. Results: A total of 57 respondents (82.6%) had a high level of knowledge, 10 respondents (14.5%) had a moderate level of knowledge, and 2 respondents (2.9%) had a low level of knowledge regarding anemia. Conclusion: Most students at the Faculty of Health Sciences Universitas Nahdlatul Ulama Sumatera Utara, have a high level of knowledge about anemia.